2017
DOI: 10.1088/1361-6528/aa9abe
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent surface plasmon resonance of ITO nanoparticles for ITO/In-Sn bilayer structure

Abstract: Tuning the localized surface plasmon resonance (LSPR) in doped semiconductor nanoparticles (NPs), which represents an important characteristic in LSPR sensor applications, still remains a challenge. Here, indium tin oxide/indium tin alloy (ITO/In-Sn) bilayer films were deposited by electron beam evaporation and the properties, such as the LSPR and surface morphology, were investigated by UV-VIS-NIR double beam spectrophotometer and atomic force microscopy (AFM), respectively. By simply engineering the thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Due to the wide energy gap, conventional semiconductor materials need to absorb UV light with higher energy to excite the electrons and release heat in the process of falling back to the ground state. However, with the study of more kinds of semiconductor materials, it has been found that localized surface plasmon resonance (LSPR) exists not only in noble metals, but also in semiconductor materials with appreciable free carrier density, such as tin-doped indium oxide (ITO) [ 66 , 67 ], copper sulfide (Cu x S) [ 68 , 69 ], titanium nitride (TiN) [ 70 , 71 ], etc. Compared with conventional noble metals, semiconductors can exhibit LSPR in both the ultraviolet-visible (UV-vis) and near–mid-infrared (IR) spectral regions, which significantly extends the light absorption range.…”
Section: Common Photothermal Conversion Materialsmentioning
confidence: 99%
“…Due to the wide energy gap, conventional semiconductor materials need to absorb UV light with higher energy to excite the electrons and release heat in the process of falling back to the ground state. However, with the study of more kinds of semiconductor materials, it has been found that localized surface plasmon resonance (LSPR) exists not only in noble metals, but also in semiconductor materials with appreciable free carrier density, such as tin-doped indium oxide (ITO) [ 66 , 67 ], copper sulfide (Cu x S) [ 68 , 69 ], titanium nitride (TiN) [ 70 , 71 ], etc. Compared with conventional noble metals, semiconductors can exhibit LSPR in both the ultraviolet-visible (UV-vis) and near–mid-infrared (IR) spectral regions, which significantly extends the light absorption range.…”
Section: Common Photothermal Conversion Materialsmentioning
confidence: 99%
“…In recent years, researchers have been increasingly interested in new plasmonic nanoparticles to improve the PCE of solar cells, which is indium tin oxide nanoparticles (ITO NPs). ITO NPs, known as crystalline nanomaterials with a wide bandgap, show low electrical resistance and light trapping [29][30][31]. They were used as a rear surface of a silicon solar cell [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…33 The impacts of the LSPR in the ITO substrate include surface enhancement and shape-controlled extinction, in particular, with different widths of ITO, as reported by Rhodes et al, in 2008, who investigated the optical characteristics of ITO with increasing thickness from 30 to 300 nm 34 and by Wei et al, in 2017, who discovered that the LSPR wavelength of ITO was tunable within the range from 858 to 1758 nm through a simple engineering of ITO/In-Sn NP thickness. 35 Moreover, ITO is chemically stable and particularly easy to use in some deposition methods, such as in sputtering. Additionally, some approaches to modifying ITO, such as the fabrication of a grated ITO substrate, showed great tolerance to deviations in fabrication due to its large refractive index contrast.…”
Section: Introductionmentioning
confidence: 99%